2022
DOI: 10.19044/esj.2022.v18n21p120
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Water Stress on the Agromorphological Parameters of Two New Maize (Zea mays L.) Lines (L36 and L71) Obtained from the Variety EV8728

Abstract: Maize (Zea mays L.) or Indian wheat is the most cultivated cereal in the world and the first in terms of quantity before wheat. Its cultivation is confronted with the climate change which causes drought, and this last one reduces considerably its production. The objective of this experiment is to select maize (Zea mays L.) varieties resistant to water stress using gamma irradiation. Its aim is to characterize agromorphologically two maize lines derived from the gamma irradiated variety EV8728. This study took … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…The WD1 condition allowed some yield recovery depending on the variety, with variety 11, for example, producing a sufficient yield comparable to WW results. The effects of water stress on plant height are well studied, and the results found in our study are consistent with those found in the literature for miscanthus and maize ( Emerson et al., 2014 ; Néné-bi et al., 2022 ), and also for sorghum and sugarcane ( dos Santos et al., 2015 ; Perrier et al., 2017 ). We hypothesize that one of the reasons for the reduction in total plant height under water stress is the reduction in internode length, as noted by Sah et al., 2020 .…”
Section: Discussionsupporting
confidence: 93%
“…The WD1 condition allowed some yield recovery depending on the variety, with variety 11, for example, producing a sufficient yield comparable to WW results. The effects of water stress on plant height are well studied, and the results found in our study are consistent with those found in the literature for miscanthus and maize ( Emerson et al., 2014 ; Néné-bi et al., 2022 ), and also for sorghum and sugarcane ( dos Santos et al., 2015 ; Perrier et al., 2017 ). We hypothesize that one of the reasons for the reduction in total plant height under water stress is the reduction in internode length, as noted by Sah et al., 2020 .…”
Section: Discussionsupporting
confidence: 93%
“…In the literature, it is widely recognized that DM and CW digestibilities in grasses increase with the water deficit (Emerson et al ., 2014; dos Santos et al ., 2015; El Hage et al ., 2018; Néné-bi et al ., 2022; Main et al ., 2023). However, the results of the severe stress experienced in 2022 indicate that we have reached a new response threshold for DM digestibility under the combined effect of severe water and heat stress.…”
Section: Discussionmentioning
confidence: 99%